(untitled) (Praxis Educativa, 2012)
This paper reviews the findings of a master’s thesis directed by Dr. Edith Litwin called “Learning in Alto Valle de Rio Negro and Neuquén High Schools in the opinion of college students from the Universidad National of Comahue”. The students interviewed studied in high school during from 2000 to 2005. From cognitive and constructivist approaches to socio-cognitive learning, we carried out research into the significance of advanced university students’ learning in high school. We focus on narratives related to: What aspects of learning practice in high schools students recover as its constitutive part? What projection value do they assign to acquired learning? We interpreted the significance of the history of learning practice in High School, the formats of interaction between this practice and teaching practice, the link between learning practice and the institutional environment.